Effect of Imidazoline Drugs on Human Blood Platelet Aggregation - Petrusewicz, Jacek; Kaliszan, Roman (Thrombosis and Haemostasis, 1985)
The effect of seven commonly used in therapy imidazoline derivatives on human blood platelet aggregation was studied. Three of the agents, i.e. clonidine, antazoline and tetryzoline were classified as partial agonists of the receptor responsible for aggregation. Two other drugs, i.e. phentolamine and tolazoline act as competitive antagonists of relatively high receptor affinity. The remaining imidazolines: xylometazoline and naphazoline effectively inhibit the platelet receptor in a non-competitive manner. The last two compounds seem to be selective alpha2-adrenoceptor antagonists.
Keywords: Platelet aggregation; Imidazoline drugs; effect on; Alpha2-adrenoceptors